Study of water droplet impinging on surface - Ow, Zhi Wei (Nanyang Technological University, 2022)
This report presents experimental investigations of the impact dynamics of droplet impingement and spreading characteristics on moving superhydrophobic surfaces, with varying degrees of incline and surface velocity through means of a high-speed camera. The study on the topic of droplet impingement has been studied by researchers for the past hundreds of years. There are many applications that droplet impingement applies to, which include many industrial applications for instance, thermal spray coating, ink-jet printing, and anti-icing purposes. The study of droplet impingement allows researchers or manufacturers to come up with better products that can be used to improve the heat transfer rate of surfaces such as for engine cooling purposes. In this study, the Phantom V711 Digital High-Speed Camera which is capable of capturing up to more than a million frames per second is utilized to capture the entire impingement process. The high-speed camera provides a wide range of high-resolution images and videos that can be used to carry out further analysis. The two variable parameters in the experiment are: (1) the tangential velocity of the surface, (2) the angle of incline of the moving surface. The video recordings captured by the high-speed camera will then be processed and analyzed through the use of various software such as Phantom Camera Control (PCC) and ImageJ. It is observed that the two parameters significantly affect the spreading factor and the contact time. The increase in tangential velocity promotes the maximum spreading for all angles. The droplet rebounds off the surface at a point behind the initial impact position for moving flat superhydrophobic surfaces. When the angle of inclination is introduced, the droplet rebounds off the surface at a point in front of the initial impact position, this point gets further away from the droplet’s initial impact position as the angle of inclination is increased. The contact time decreases when the angle of incline becomes steeper on the stationary inclined superhydrophobic surfaces. However, for moving inclined superhydrophobic surfaces, the contact time increases at low tangential velocities, decreasing as the tangential velocity gradually increases. For a particular angle of incline, the increase in tangential velocity reduces contact time until it reaches a critical value. The increase in tangential velocity beyond this value will result in a further reduction in contact time. The impinged droplet leaves the surface at a point relatively close to each other when tangential velocity is introduced.